A thermal interface material and its preparation method and application

By combining carbon nanotubes, carbon fibers with polymers, and using electrospinning and lamination processes to prepare thermal interface materials, the problem of poor mechanical properties and flexibility when improving thermal conductivity is solved, and the high thermal conductivity and excellent mechanical properties are achieved.

CN119775775APending Publication Date: 2025-04-08FOSHAN QINGLI NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411702502.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

While the existing high-thermal conductivity thermal interface materials improve thermal conductivity, their mechanical properties and flexible elasticity are poor, making it difficult to meet the needs of high thermal conductivity and excellent mechanical properties at the same time.

Method used

The intermediate was obtained by mixing carbon nanotubes, carbon fibers and silane coupling agent, and then electrospinned with a polymer solution to form an oriented film, and a thermal interface material was prepared by lamination and pressurized curing.

Benefits of technology

It realizes high thermal conductivity, excellent mechanical properties and high flexibility of thermal interface materials, and can provide better thermal management performance in electronic products, chips, high-power devices, medical equipment and aerospace devices.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a thermal interface material and a preparation method and application thereof; the preparation method comprises the following steps: S1, mixing carbon nanotubes, carbon fibers, solvent I and silane coupling agent, ultrasonic I, and drying to obtain an intermediate; S2, mixing the intermediate, polymer and solvent II, ultrasonic II to obtain a spinning solution; electrostatic spinning the spinning solution to obtain a film; S3, placing the film into a mold for lamination, injecting a curable resin, and pressurizing and curing; and slicing along the cross-sectional direction to obtain the thermal interface material. The thermal interface material prepared by the method has excellent thermal conductivity, elasticity and mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, and in particular to a thermal interface material and a preparation method and application thereof. Background Art

[0002] As spacecraft, electronic terminal products, etc. continue to develop towards super-large, miniaturized, high-performance, light, thin, and multi-functional trends, the requirements for efficient heat transfer and heat dissipation, thermal stability, etc. are becoming increasingly higher, and the demand for high thermal conductivity materials with higher thermal conductivity is also increasing.

[0003] At present, high thermal conductivity thermal interface materials are generally prepared by adding carbon fiber to an organic matrix system such as silicone rubber to make high thermal conductivity gaskets. However, by mixing carbon fiber and silicone rubber, the amount added to the system is limited, which limits the improvement of thermal conductivity. In addition, the higher the amount added, the worse the mechanical properties and the lower the flexibility. When it can meet the requirements of excellent mechanical properties and flexibility, the thermal conductivity is poor.

[0004] Therefore, it is necessary to develop a preparation method of a thermal interface material with good mechanical properties and high thermal conductivity. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the first aspect of the present invention provides a method for preparing a thermal interface material, wherein the thermal interface material prepared by the method has the characteristics of high thermal conductivity and mechanical properties.

[0006] The second aspect of the present invention also provides a thermal interface material.

[0007] The third aspect of the present invention also provides an application of a thermal interface material.

[0008] According to a first aspect of the present invention, a method for preparing a thermal interface material is provided, comprising the following steps:

[0009] S1, mixing carbon nanotubes, carbon fibers, solvent I and silane coupling agent, ultrasonically performing I, and drying to obtain an intermediate;

[0010] S2, mixing the intermediate, polymer and solvent II by ultrasonic II to obtain a spinning solution; and electrospinning the spinning solution to obtain a film;

[0011] S3, placing the film into a mold for lamination, injecting a curable resin, and pressurizing and curing the film; and slicing the film along the cross-sectional direction.

[0012] The method for preparing the thermal interface material according to the embodiment of the present invention has at least the following beneficial effects:

[0013] The present invention prepares a thermal interface material by mixing carbon nanotubes, carbon fibers and a coupling agent to obtain an intermediate, then mixing the intermediate with a polymer solution for electrostatic spinning, and then laminating and pressurizing the film for solidification and slicing; the thermal interface material has excellent thermal conductivity, elasticity and mechanical properties.

[0014] Furthermore, the composite of carbon fiber and carbon nanotube of the present invention can help to better disperse it in polymer and increase the filling amount. The prepared intermediate is mixed with polymer to form spinning solution, and a film is obtained by electrostatic spinning. The film prepared by this method not only realizes directional arrangement of carbon nanotubes and carbon fibers under the action of electric field, but also promotes the disentanglement of polymer chains in the interaction between carbon nanotubes and carbon fibers and polymers during ultrasonic dispersion, and further drives the polymer chains to have a certain orientation in the directional movement of carbon nanotubes and carbon fibers in the electric field, thereby improving the thermal conductivity of the film as a whole in the orientation direction.

[0015] Furthermore, the intermediate is made into an oriented film through an electrospinning process, so that the polymer will have orientation. At the same time, due to the interaction between the orientation of the polymer and the electrospinning process, the carbon fibers and carbon nanotubes also form an oriented arrangement, and the entire film is continuously oriented. The film is a whole as the final oriented heat transfer path. The prepared films are then stacked in sequence, and the stacking effect can further improve the thermal conductivity and flexibility.

[0016] According to a preferred embodiment of the present invention, in step S2, the amount of the intermediate is 5wt.% to 50wt.% of the amount of the polymer, for example, 5wt.%, 10wt.%, 15wt.%, 20wt.%, 30wt.%, 40wt.%, 50wt.% or a sub-range consisting of any two values.

[0017] According to a preferred embodiment of the present invention, the polymer is selected from at least one of polyvinyl alcohol (PVA), polyacrylonitrile (PAN), polyethylene terephthalate (PET) or polyimide (PI).

[0018] According to a preferred embodiment of the present invention, the curable resin is selected from at least one of addition silicone rubber, acrylate, epoxy resin or polyurethane.

[0019] According to a preferred embodiment of the present invention, the amount of the silane coupling agent used is 0.05wt.% to 5wt.% of the total mass of the carbon nano-particles and the carbon fibers.

[0020] According to a preferred embodiment of the present invention, in step S1, the mass ratio of the carbon fiber to the carbon nanotube is 1:(1-5).

[0021] According to a preferred embodiment of the present invention, in step S2, the voltage of the electrospinning is 5KV to 30KV.

[0022] According to a preferred embodiment of the present invention, in step S3, the pressure of the pressurized curing is 80-200 psi; and / or the temperature is 70-90°C.

[0023] According to a preferred embodiment of the present invention, the silane coupling agent is selected from at least one of 3-aminopropyltrimethoxysilane, 3-(acryloxy)propyltrimethoxysilane, vinyltrimethoxysilane, γ-aminopropyltriethoxysilane and γ-glycidyloxypropyltrimethoxysilane.

[0024] According to a preferred embodiment of the present invention, the solvent I is selected from at least one of N-methylpyrrolidone, anhydrous ethanol, ethylene glycol, dichloromethane and acetone.

[0025] According to a preferred embodiment of the present invention, the solvent II is selected from at least one of dimethylformamide, water, dimethyl sulfoxide, sulfolane, and ethyl nitrate.

[0026] According to a preferred embodiment of the present invention, the carbon nanotubes are selected from single-arm carbon nanotubes, and the single-arm carbon nanotubes have a diameter of 0.5 to 100 nm and a length of 1 to 30 μm.

[0027] According to a preferred embodiment of the present invention, the length of the carbon fiber is 50-400 μm.

[0028] According to a preferred embodiment of the present invention, the duration of the ultrasound I is 1 to 4 hours.

[0029] According to a preferred embodiment of the present invention, the frequency of the ultrasound I is 100-1500 Hz.

[0030] According to a preferred embodiment of the present invention, the duration of ultrasound II is 2 to 5 hours.

[0031] According to a preferred embodiment of the present invention, the frequency of the ultrasound II is 100-1500 Hz.

[0032] According to a preferred embodiment of the present invention, there is no limitation on the number of layers of the stack, and the number of layers can be selected according to actual needs, such as 50 layers, 100 layers, 150 layers, 200 layers, etc.

[0033] According to the second aspect of the present invention, a thermal interface material is provided, which is prepared by the preparation method described in the first aspect of the present invention. Thus, the prepared thermal interface material has excellent thermal conductivity and mechanical properties.

[0034] The third aspect of the present invention provides an application of the thermal interface material described in the second aspect of the present invention in the fields of electronic products, chips, high-power devices, medical equipment and aerospace devices.

[0035] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be obvious from the description, or may be learned by practice of the present invention. DETAILED DESCRIPTION

[0036] The following are specific embodiments of the present invention, and the technical solutions of the present invention are further described in conjunction with the embodiments, but the present invention is not limited to these embodiments.

[0037] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0038] The raw materials used in the examples and comparative examples of the present invention are as follows:

[0039] Two-component addition silicone rubber: the mass ratio of vinyl silicone oil (A): vinyl silicone oil + hydrogenated silicone oil + inhibitor (B) is 1:1; the viscosity of the two-component mixture before curing is 1000cps, and the hardness of the two-component mixture after curing is shore00 70;

[0040] Curable two-component liquid polyurethane: the mass ratio of polyester polyol (A): isocyanate (B) is 10:1; the two-component mixed viscosity before curing is 1000cps, and the hardness after curing after the two-component mixing is shoreA30;

[0041] Single-arm carbon nanotube: diameter 1-3nm, length 5-30um, SG65i;

[0042] Carbon fiber: diameter 11um, length 200-250um; LG Chemical;

[0043] Silane coupling agent: 3-aminopropyltrimethoxysilane; Dow Corning;

[0044] PVA: polyvinyl alcohol, Japan Kuraray;

[0045] PAN: polyacrylonitrile; Toray, Japan.

[0046] Example 1

[0047] This example provides a thermal interface material, and the preparation method thereof is as follows:

[0048] S1, 10g of single-walled carbon nanotubes and 10g of 250um long carbon fibers were added to 100g of NMP respectively, and dispersed for 2h by ultrasonic probe, and then the two dispersions were mixed and 0.2g of 3-aminopropyltrimethoxysilane was added, and the dispersion was continued for 1h, and the dispersed mixture was filtered and dried at 80°C to obtain an intermediate;

[0049] S2. Weigh 100g of PVA and dissolve it in 1000g of water, heat it to 60°C, stir it for 4h to obtain a 10% PVA aqueous solution, use a probe ultrasonic instrument to ultrasonicate the PVA aqueous solution at a power of 600W for 1.5h, then add 5g of the intermediate to the PVA aqueous solution and ultrasonically disperse it for 2h to obtain a spinning solution; load the spinning solution into a generator, adjust the distance between the two parallel electrodes of the electrospinning collecting plate to 12cm, set the electrospinning voltage to 12KV, and perform electrospinning.

[0050] S3. Put 100 layers of film stack prepared by electrospinning into a molding mold, inject two-component addition-type silicone rubber into the mold; pressurize to 100 psi and heat to 80°C for curing for 24 hours, and then cut 1 mm thick along the cross-sectional direction to obtain the obtained film.

[0051] Example 2

[0052] This example provides a thermal interface material, and the preparation method thereof is as follows:

[0053] S1, adding 10g of single-walled carbon nanotubes and 10g of 250um long carbon fibers into 200g of NMP, adding 0.2g of 3-aminopropyltrimethoxysilane, dispersing for 2h by ultrasonic probe, filtering the dispersed mixed solution, and drying at 80°C to obtain an intermediate;

[0054] S2. Weigh 100g of PVA and dissolve it in 1000g of water, heat it to 60°C, stir it for 4h to obtain a 10% PVA aqueous solution, use a probe ultrasonic instrument to ultrasonicate the PVA aqueous solution at a power of 600W for 1.5h, then add 10g of the intermediate to the PVA aqueous solution and ultrasonically disperse it for 2h to obtain a spinning solution; load the spinning solution into a generator, adjust the distance between the two parallel electrodes of the electrospinning collecting plate to 12cm, set the electrospinning voltage to 12KV, and perform electrospinning.

[0055] S3. Put 100 layers of film stack prepared by electrospinning into a molding mold, inject two-component addition-type silicone rubber into the mold; pressurize to 100 psi and heat to 80°C for curing for 24 hours, and then cut 1 mm thick along the cross-sectional direction to obtain the obtained film.

[0056] Example 3

[0057] This example provides a thermal interface material, and the preparation method thereof is as follows:

[0058] S1, adding 10g of single-walled carbon nanotubes and 10g of 250um long carbon fibers into 200g of NMP, adding 0.2g of 3-aminopropyltrimethoxysilane, dispersing for 2h by ultrasonic probe, filtering the dispersed mixed solution, and drying at 80°C to obtain an intermediate;

[0059] S2. Weigh 100g of PVA and dissolve it in 1000g of water, heat it to 60°C, stir it for 4h to obtain a 10% PVA aqueous solution, use a probe ultrasonic instrument to ultrasonicate the PVA aqueous solution at a power of 600W for 1.5h, then add 15g of the intermediate to the PVA aqueous solution and ultrasonically disperse it for 2h to obtain a spinning solution; load the spinning solution into a generator, adjust the distance between the two parallel electrodes of the electrospinning collecting plate to 12cm, set the electrospinning voltage to 12KV, and perform electrospinning.

[0060] S3. Put 100 layers of film stack prepared by electrospinning into a molding mold, inject two-component addition-type silicone rubber into the mold; pressurize to 100 psi and heat to 80°C for curing for 24 hours, and then cut 1 mm thick along the cross-sectional direction to obtain the obtained film.

[0061] Example 4

[0062] This example provides a thermal interface material, and the preparation method thereof is as follows:

[0063] S1, adding 15g of single-walled carbon nanotubes and 10g of 250um long carbon fibers into 200g of NMP, adding 0.2g of 3-aminopropyltrimethoxysilane, dispersing for 2h by ultrasonic probe, filtering the dispersed mixed solution, and drying at 80°C to obtain an intermediate;

[0064] S2. Weigh 100g of PVA and dissolve it in 1000g of water, heat it to 60°C, stir it for 4h to obtain a 10% PVA aqueous solution, use a probe ultrasonic instrument to ultrasonicate the PVA aqueous solution at a power of 600W for 1.5h, then add 10g of the intermediate to the PVA aqueous solution and ultrasonically disperse it for 2h to obtain a spinning solution; load the spinning solution into a generator, adjust the distance between the two parallel electrodes of the electrospinning collecting plate to 12cm, set the electrospinning voltage to 12KV, and perform electrospinning.

[0065] S3. Put 100 layers of film stack prepared by electrospinning into a molding mold, inject two-component addition-type silicone rubber into the mold; pressurize to 100 psi and heat to 80°C for curing for 24 hours, and then cut 1 mm thick along the cross-sectional direction to obtain the obtained film.

[0066] Example 5

[0067] This example provides a thermal interface material, and the preparation method thereof is as follows:

[0068] S1, adding 10g of single-walled carbon nanotubes and 10g of 250um long carbon fibers into 200g of NMP, adding 0.2g of 3-aminopropyltrimethoxysilane, dispersing for 2h by ultrasonic probe, filtering the dispersed mixed solution, and drying at 80°C to obtain an intermediate;

[0069] S2. Weigh 100 g of PAN and dissolve it in 1000 g of NMP, heat it to 60°C, stir it for 2 h, use a probe ultrasonic instrument to ultrasonicate at 600 W for 1.5 h, then add 10 g of the intermediate to the PAN solution and ultrasonically disperse it for 2 h to obtain a spinning solution; load the spinning solution into the generator, adjust the distance between the two parallel electrodes of the electrospinning collecting plate to 12 cm, set the electrospinning voltage to 14 KV, and perform electrospinning.

[0070] S3. Put 100 layers of film stack prepared by electrospinning into a molding mold, inject two-component addition-type silicone rubber into the mold; pressurize to 100 psi and heat to 80°C for curing for 24 hours, and then cut 1 mm thick along the cross-sectional direction to obtain the obtained film.

[0071] Example 6

[0072] This example provides a thermal interface material, and the preparation method thereof is as follows:

[0073] S1, adding 10g of single-walled carbon nanotubes and 10g of 250um long carbon fibers into 200g of NMP, adding 0.2g of 3-aminopropyltrimethoxysilane, dispersing for 2h by ultrasonic probe, filtering the dispersed mixed solution, and drying at 80°C to obtain an intermediate;

[0074] S2. Weigh 100 g of PAN and dissolve it in 1000 g of NMP, heat it to 60°C, stir it for 2 h, use a probe ultrasonic instrument to ultrasonicate at 600 W for 1.5 h, then add 10 g of the intermediate to the PAN solution and ultrasonically disperse it for 2 h to obtain a spinning solution; load the spinning solution into the generator, adjust the distance between the two parallel electrodes of the electrospinning collecting plate to 12 cm, set the electrospinning voltage to 14 KV, and perform electrospinning.

[0075] S3. Put 100 layers of film stack prepared by electrospinning into a molding mold, inject curable two-component liquid polyurethane into the mold; pressurize to 100 psi and heat to 80°C for curing for 24 hours, and then cut 1 mm thick along the cross-sectional direction to obtain the obtained film.

[0076] Comparative Example 1

[0077] This example provides a thermal interface material, and its preparation method is the same as that of Example 4, except that the single-walled carbon nanotubes are 12g; and carbon fibers are not included.

[0078] Comparative Example 2

[0079] This example provides a thermal interface material, and its preparation method is the same as that of Example 4, except that the carbon fiber is 20g and does not contain carbon nanotubes.

[0080] Performance Testing

[0081] The thermal interface materials prepared in Examples 1 to 5 of the present invention and Comparative Examples 1 to 2 were subjected to the following tests:

[0082] Thermal conductivity and thermal resistance were tested according to ASTM D5470 (2017);

[0083] Compression rate is tested according to ASTM D575 (2024);

[0084] The tensile strength was tested according to ASTM D412 (2021). The results are shown in Table 1.

[0085] Table 1

[0086] Thermal conductivity / W / (m·K) Thermal resistance / cm^2K / W Compression rate / % Tensile strength / MPa Example 1 15.8 0.49 40 0.1 Example 2 21.3 0.46 30 0.13 Example 3 19.2 0.63 21 0.14 Example 4 18 0.7 20 0.14 Example 5 23.6 0.42 32 0.11 Example 6 19.3 0.5 25 0.3 Comparative Example 1 9.1 0.97 45 0.08 Comparative Example 2 13.7 0.8 22 0.13

[0087] From the data in Table 1, the thermal interface materials prepared in Examples 1 to 6 of the present invention can have high elasticity and flexibility while having high thermal conductivity. This is because the present invention uses a filler composed of carbon fiber and carbon nanotubes and a polymer mixture, and the mixed polymer is made into an oriented film through an electrostatic spinning process, so that the polymer has orientation. At the same time, due to the combined effect of the orientation of the polymer and the electrostatic spinning process, the carbon fiber and carbon nanotubes also form an oriented arrangement, and the entire film is a continuous conductive orientation. The film is a whole as the final oriented heat transfer path. Furthermore, the prepared film is stacked in sequence, and the effect of stacking can further improve the thermal conductivity and flexibility.

[0088] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.

Claims

1. A method for preparing a thermal interface material, characterized in that: The steps include: S1, mixing carbon nanotubes, carbon fibers, solvent I and silane coupling agent, ultrasonically performing I, and drying to obtain an intermediate; S2, mixing the intermediate, polymer and solvent II by ultrasonic II to obtain a spinning solution; and electrospinning the spinning solution to obtain a film; S3, placing the film into a mold for lamination, injecting curable resin, and pressurizing and curing; The sample is obtained by slicing along the cross-sectional direction.

2. The method for preparing a thermal interface material according to claim 1, characterized in that: In step S2, the amount of the intermediate used is 5wt.% to 50wt.% of the amount of the polymer used.

3. The method for preparing a thermal interface material according to claim 1, characterized in that: The polymer is selected from at least one of PVA, PAN, PET or PI.

4. The method for preparing a thermal interface material according to claim 1, characterized in that: The curable resin is selected from at least one of addition silicone rubber, acrylate, epoxy resin or polyurethane.

5. The method for preparing a thermal interface material according to claim 1, characterized in that: The amount of the silane coupling agent used is 0.05wt.% to 5wt.% of the total mass of the carbon nano-particles and the carbon fibers.

6. The method for preparing a thermal interface material according to claim 1, characterized in that: In step S1, the mass ratio of the carbon fiber to the carbon nanotube is 1:(1-5).

7. The method for preparing a thermal interface material according to claim 1, characterized in that: In step S2, the voltage of the electrospinning is 5KV to 30KV.

8. The method for preparing a thermal interface material according to claim 1, characterized in that: In step S3, the pressure of the pressurized curing is 20-200 psi; and / or the temperature is 50-150°C.

9. A thermal interface material, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 8.

10. Application of the thermal interface material according to claim 9 in the fields of electronic products, chips, high-power devices, medical equipment and aerospace devices.